If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 = 2x + -9 Reorder the terms: -21 = -9 + 2x Solving -21 = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -21 + -2x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 -21 + -2x = -9 + 0 -21 + -2x = -9 Add '21' to each side of the equation. -21 + 21 + -2x = -9 + 21 Combine like terms: -21 + 21 = 0 0 + -2x = -9 + 21 -2x = -9 + 21 Combine like terms: -9 + 21 = 12 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| 191-v=89 | | -3(r+6)=-58 | | 3x+2=3(4)+2 | | 4y-4=35-6y | | z^4=28+96i | | 2x-18=3x+8 | | 231=165-y | | x=-12+-3y | | 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 | | 5x+4-8=18 | | 3n^2=-4n-1 | | 5(3k+2)=40 | | 6x-5+2x+43=90 | | 3+2(x+2)=15 | | 3(2y+1)=39 | | 2x+8=x+11 | | X=-0.5x+3 | | -7(2t+8)=-126 |